A percepção de auditores do Tribunal de Contas do Estado do Rio Grande do Sul sobre a transparência pública - Bortulini, Emanuel Felipe (Universidade do Vale do Rio dos Sinos, 2016)
In recent years the Brazilian government has increased the disclosure of public institutions data, as required by the Access to Information Law. Federal, state and city governments now have to present evidence of their efficacy, efficiency, effectiveness and ethics in public administration. The Brazilian society can oversight many instances of the public administration and increase its social control. This research evaluates the perception of the external public auditors at the Auditor’s Court of the State of Rio Grande do Sul (TCE-RS) about the quality, sufficiency, and usefulness of the available information, systems and procedures. A sample of 131 auditors responded a survey and semi-structured interviews were applied to 10 audit coordinators in each of the TCE-RS' regional units. Results show that auditors and coordinators believe that the data available to the public have adequate frequency and format, but it is insufficient to effective social control, which is partially explained by the lack of comprehension of the public and by the absence of uniformity among government's reports and websites. Nevertheless, auditors and coordinators perceive an increasing use of public transparency instruments and systems, and find it useful to their internal tasks, in particular when the information is gathered together.
Keywords: Accountability; Auditoria; Controle social; Governança pública; Transparência; Audit; Social control; Public governance; Transparency; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis